The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1057/s41285-019-00122-z
|View full text |Cite
|
Sign up to set email alerts
|

Explaining mental health recovery in the context of structural disadvantage: the unrealised potential of critical realism

Abstract: Despite the acknowledgement that mental health inequalities are shaped by the interaction of macro-level (structural) and micro-level (individual, agentic) powers, dominant paradigms in mental health research have been ill-equipped to integrate those different levels of influence theoretically and empirically. As a result, an 'explanatory deficit' persists as to the causal mechanisms underpinning the impact of social inequalities on mental well-being, particularly mental health recovery. To redress this gap, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Leamy’s personal recovery framework CHIME (Connectedness, Hope and optimism, Identity, Meaning, Empowerment) is one such model [ 55 ]. However, recent research has argued that such models cannot address structural disadvantages or social marginalisation that a person with SMI might face [ 56 ]. Current models also fail to capture the organisational barriers that need addressing in order to promote recovery-oriented care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leamy’s personal recovery framework CHIME (Connectedness, Hope and optimism, Identity, Meaning, Empowerment) is one such model [ 55 ]. However, recent research has argued that such models cannot address structural disadvantages or social marginalisation that a person with SMI might face [ 56 ]. Current models also fail to capture the organisational barriers that need addressing in order to promote recovery-oriented care.…”
Section: Discussionmentioning
confidence: 99%
“…Aside the above three elements of the framework, it is important to identify and tackle the root causes such as discrimination, social stigma and resultant isolation, unemployment-generated poverty, and social inequality that perpetuate poor health conditions in people with SMI. Recent research has demonstrated that personal recovery models do not reflect these broader social structural problems [ 53 , 56 , 65 ], and as a result, fail to achieve sustainable outcomes. Trauma and iatrogenic trauma are other dismaying causes that require close attention if we want genuine changes in service users’ health behaviours [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can be thought of as “potentialities” inherent in structures which might manifest overtly. That is, depending on the conditions that facilitate the actualization of a structure's causal potential, they may or may not have an observable impact at the empirical level (Karadzhov, 2019). Some of this insight stems from the identification of deep generative processes as vertical explanations recognized between the layers of stratified reality we have previously discussed—the real, actual, and empirical levels.…”
Section: Critical Realismmentioning
confidence: 99%
“…Deepening our understanding of how structural factors trickle down to poor personal well‐being, marginalization, and welfare should therefore become an urgent priority (Karadzhov, 2019). For the purposes of this paper “structural” or “structures” refer to social relations (economic–political–cultural–affective) which have causal powers, capable of change, continuous reproduction and transformation which can be seen or unseen in how they impact individual agency (Jones, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…By examining the agency-structure nexus, critical realist and the capabilities approach informed research could help illuminate the role of structural configurations that generate inequality, impede clinical recovery, and limit the embodied experience of the aspects of personal recovery we identified. Such research may further clarify the clinical-personal recovery relationship, help identify and remove oppressive structures, and guide ameliorative social change [55,56]. As clinical recovery's influence may differ depending when meaning-making occurs, studies exploring the relationship at different time points post psychiatric diagnosis would be helpful.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%